Recollecting Resonances Indonesian-Dutch Musical Encounters - Barendregt, Bart; Bogaerts, Els (Southeast Asia Mediated, 2013)
Over time Dutch and Indonesian musicians have inspired each other and they continue to do so. Recollecting Resonances offers a way of studying these musical encounters and a mutual heritage one today still can listen to. Readership: All those willing to learn more about the impact and consequences of musical encounters between Dutch and Indonesian performers in both a colonial and postcolonial setting as well as those with a wider interest in cultural and musical studies.